Copper alloy plate strip for multi-component synergistically reinforced lead frame and preparation method of copper alloy plate strip
Through the multi-component collaborative strengthening process method, copper alloy plate and tape were prepared, which solved the shortcomings of domestic Cu-Ni-Si alloys in heat treatment technology, and achieved high-performance copper alloy plate and tape, meeting the needs of mid-to-high-end lead frame materials.
Patent Information
- Application Number
- CN202510108677.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-23
AI Technical Summary
Domestic Cu-Ni-Si alloys have shortcomings in the control of the composition uniformity of large-scale ingot components, continuous high-temperature online solution and complete sets of heat treatment technologies, resulting in poor surface quality, high surface roughness, unstable plate accuracy, and low quality grade, which cannot meet the needs of mid-to-high-end lead frame materials.
The process method of multi-component collaborative strengthening is adopted to prepare copper alloy plate strips, including ingredients, smelting, solid solution, hot rolling and cold rolling. By controlling elemental composition and process parameters, the mechanical properties and conductive properties of the alloy are improved.
The tensile strength, conductivity and yield strength of the copper alloy plate strip are achieved at 850Mpa, 48% IACS and 750MPa or above. The strip is uniform in chemical composition, excellent mechanical properties and conductive properties, simple preparation process and low operation difficulty.
Smart Images

Figure CN119876689A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy materials, and in particular to a copper alloy strip for a multi-component synergistically reinforced lead frame and a preparation method thereof. Background Art
[0002] As an important component of integrated circuits, lead frames play a key role in supporting chips, connecting circuits, and distributing power. With the rapid development of integrated circuits towards large and extremely large scales, circuit integration and high density have put forward higher requirements on the accuracy, surface quality and plate shape of lead frame materials, and they must have good thermal conductivity, electrical conductivity, high strength, elasticity, and bending resistance.
[0003] Foreign enterprises started early, developed rapidly and achieved high technical maturity in the development of lead frame materials. For example, Japanese Mitsubishi Shindoh, Furukawa, Nippon Mining, Sumitsu Seiko, Diehl, American Olin, German Wieland and other enterprises all have their own Cu-Ni-Si alloy grades, and use semi-continuous casting, hot rolling, solid solution aging treatment and other technical routes to achieve alloy industrialization, establish multiple highly automated production lines, stable product performance, high added value, and become the world's main supplier of high-end lead frame strip materials. In 2019, the total amount of domestic copper strips was close to 2.87 million tons, of which the output of copper strips for lead frames was less than 100,000 tons, mainly low-end lead frame materials of KFC and C19400 alloys, and a small amount of Cu-Ni-Si lead frame materials. The domestic demand for lead frame materials is close to 150,000 tons, of which most of the mid-to-high-end lead frame materials are mainly imported. At present, only Ningbo Xingye, Chalco Luotong, Ningbo Bowei and other companies have realized the industrialization of Cu-Ni-Si series alloys by semi-continuous casting, with an annual output of less than 5,000 tons. The domestically industrialized production is Cu-3.2%Ni-0.6%Si-0.06%Mg (C70250) and Cu-1.5Ni-0.25Si-0.03P (C19010) alloys, among which C70250 is currently only achieved by a few domestic companies. This is mainly due to the high content of nickel and silicon elements, which requires a high set of heat treatment technology. If the control is unreasonable, it is difficult to effectively achieve the complete precipitation of the second phase particles, resulting in low comprehensive performance of the material.
[0004] At present, the main prominent problem in the industrial production of Cu-Ni-Si alloys in China is the failure to fully master the key production technologies such as the control technology of the composition uniformity of large-scale ingots of Cu-Ni-Si alloys, continuous high-temperature online solid solution and a complete set of heat treatment technologies. This has led to poor surface quality of alloy products (more than 10 small pits with a depth of 5μm within 1m), high surface roughness (0.10~0.15μm), unstable plate shape accuracy, etc., and the quality grade is low, so it can only be used for medium and low-end lead frame materials. Summary of the invention
[0005] Based on this, the present invention provides a copper alloy strip for a multi-component synergistically reinforced lead frame and a preparation method thereof. The tensile strength of the copper alloy strip of the present invention is b ≥850Mpa, conductivity ≥48%IACS, yield strength σ 0.2 ≥750MPa, the strip has uniform chemical composition, excellent mechanical properties and electrical conductivity, and its preparation process is simple.
[0006] The multi-component synergistically reinforced copper alloy strip for lead frame of the present invention comprises the following components in percentage by mass:
[0007] Ni: 0.9% ~ 3.0%; Si: 0.3% ~ 1.3%; Mg: 0.06% ~ 0.18%; Co: 0.5% ~ 1.5%; Ti: 0.02% ~ 0.1%; Y: 0.05% ~ 0.15%, the remainder is copper and unavoidable impurities.
[0008] The method for preparing the multi-component synergistically reinforced copper alloy strip for lead frame of the present invention comprises the following steps:
[0009] (1) Ingredients: Weigh titanium powder, magnesium powder, Cu-Y alloy, silicon powder, cobalt powder, nickel powder and copper powder;
[0010] (2) Melting: Weighed titanium powder, magnesium powder, and Cu-Y alloy are sealed in a pure copper tube and fixed on the robot arm of a vacuum induction furnace, and copper powder, nickel powder, silicon powder, and cobalt powder are added to the crucible of the vacuum induction furnace; after the vacuum induction furnace is evacuated, a protective atmosphere is introduced to 0.05 MPa, and then the crucible is heated until all the solids in the crucible are melted and the temperature is raised to 1500° C., the induction current is turned off, and the robot arm is quickly operated to immerse the pure copper tube containing the titanium powder, magnesium powder, and Cu-Y alloy under the melt surface, the robot arm is lifted and the induction current is turned on to continue to keep the temperature for 2 min-5 min, and casting is performed after the temperature is kept, and cooling is performed after the casting is completed to obtain an ingot;
[0011] (3) Solid solution: The ingot obtained in step (2) is subjected to surface milling treatment, and then placed in a muffle furnace and heated to 800° C. to 900° C. and kept at this temperature for 3 h to 5 h. After the heat preservation is completed, the ingot is taken out and water-cooled;
[0012] (4) Hot rolling: the solution-solution ingot is kept at 700°C to 800°C for 15 to 40 minutes, taken out and sent to a hot rolling mill for rolling with a reduction of 15% to 35% per pass, and the final rolling amount is 50%;
[0013] (5) Cold rolling: the sample after rolling in step (4) is sent to a cold rolling mill and rolled at a speed of 8% to 12% per pass to a plate thickness of 1.5 mm to 2.5 mm. The plate is then annealed at 400° C. to 450° C. for 3 h to 5 h. The plate is then rolled at a speed of 8% to 12% per pass to a plate thickness of 0.3 mm to 0.5 mm. The plate is then annealed at 300° C. to 350° C. for 3 h to 5 h. Finally, the plate is rolled at a speed of 8% to 12% per pass to a plate thickness of 0.15 mm to 0.25 mm.
[0014] Preferably, the Y content in the Cu-Y alloy is 15wt.% to 25wt.%.
[0015] Preferably, the protective atmosphere in step (2) is argon or nitrogen.
[0016] Preferably, the heating rate in step (3) is 3°C to 6°C / min.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The copper alloy strip prepared by the present invention has excellent mechanical properties and electrical conductivity, among which the tensile strength σ b ≥850Mpa, conductivity ≥48%IACS, yield strength σ 0.2 ≥750MPa.
[0019] (2) The preparation process of the present invention is simple and has low operation difficulty. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the metallographic image of the sample after solid solution in comparative example 1;
[0021] Figure 2 This is the metallographic image of the sample in the final state of Comparative Example 1;
[0022] Figure 3 This is the metallographic image of the sample after solution treatment in Example 1;
[0023] Figure 4 This is the metallographic image of the sample in the final state of Example 1. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the preferred embodiments of the present invention are further described in detail in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] 0.5g titanium powder, 1.5g magnesium powder, and 5g Cu-Y alloy (wherein the Y content is 20wt.%) are sealed in a pure copper tube and fixed on the robotic arm of a vacuum induction furnace; 938.5g copper powder, 18g nickel powder, 6.5g silicon powder, and 10g cobalt powder are added to the crucible of the vacuum induction furnace. The vacuum induction furnace was evacuated to below 15Pa, and a protective atmosphere of argon gas was introduced to 0.05MPa. Then, an induction power supply was introduced to start heating. When all the solids in the crucible were melted and the temperature rose to about 1500°C, the induction current was turned off. The robotic arm was quickly operated to immerse the pure copper tube containing titanium powder, magnesium powder, and Cu-Y alloy under the melt surface. The robotic arm was lifted, and the induction current was turned on to continue to keep warm for 3 minutes. After keeping warm, casting was carried out. After casting was completed, it was cooled for about 30 minutes and then taken out. The ingot was milled and then placed in a muffle furnace and heated to 850°C at a heating rate of 5°C / min and kept warm for 4 hours. After the insulation was completed, the ingot was taken out and water-cooled. The ingot after solid solution is placed in a muffle furnace at 800℃ for 30 minutes, taken out and sent to a hot rolling mill for a rolling process with a pressing amount of 30% per pass, and the final rolling amount is 50%. Then it is sent to a cold rolling mill and rolled at a speed of 10% per pass to a plate thickness of about 2mm, and then the plate is annealed at 430℃ for 4h, and then the plate is rolled at a speed of 10% per pass to a plate thickness of 0.45mm. Then the plate is annealed at 330℃ for 3h, and finally the plate is rolled at a speed of 10% per pass to a plate thickness of 0.2mm (the possible edge cracks are removed in time during the cold rolling process), and a multi-component synergistically strengthened copper alloy strip for lead frame is obtained.
[0027] The prepared copper alloy strip was subjected to performance tests, wherein the mass percentages of each element in the copper alloy strip are as follows:
[0028] Ni: 1.801%; Si: 6.475%; Mg: 1.426%; Co: 0.989%; Ti: 0.484%; Y: 0.089%, and the remainder is copper and inevitable impurities.
[0029] The hardness of the copper alloy strip prepared in Example 1 is HV=269.2, and the tensile strength is σ b =854.5Mpa, conductivity = 54%IACS, yield strength σ 0.2 =744MPa.
[0030] Example 2
[0031] 0.4g titanium powder, 1.0g magnesium powder, and 7.5g Cu-Y alloy (wherein the Y content is 20wt.%) are sealed in a pure copper tube and fixed on the robotic arm of a vacuum induction furnace; 934.6g copper powder, 14g nickel powder, 6.5g silicon powder, and 16g cobalt powder are added to the crucible of the vacuum induction furnace. The vacuum induction furnace was evacuated to below 15Pa, and a protective atmosphere of argon gas was introduced to 0.05MPa. Then, an induction power supply was introduced to start heating. When all the solids in the crucible were melted and the temperature rose to about 1500°C, the induction current was turned off. The robotic arm was quickly operated to immerse the pure copper tube containing titanium powder, magnesium powder, and Cu-Y alloy under the melt surface. The robotic arm was lifted, and the induction current was turned on to continue to keep warm for 3 minutes. After keeping warm, casting was carried out. After casting was completed, it was cooled for about 30 minutes and taken out. The ingot was milled and then placed in a muffle furnace and heated to 800°C at a heating rate of 5°C / min and kept warm for 5 hours. After the insulation was completed, the ingot was taken out and water-cooled. The ingot after solid solution is placed in a muffle furnace at 700℃ for 40 minutes, taken out and sent to a hot rolling mill for a rolling process with a pressing amount of 20% per pass, and the final rolling amount is 50%. Then it is sent to a cold rolling mill and rolled at a speed of 10% per pass to a plate thickness of about 2mm, and then the plate is annealed at 400℃ for 5h, and then the plate is rolled at a speed of 10% per pass to a plate thickness of 0.45mm. Then the plate is annealed at 350℃ for 4h, and finally the plate is rolled at a speed of 10% per pass to a plate thickness of 0.2mm (the possible edge cracks are removed in time during the cold rolling process), and a multi-component synergistically strengthened copper alloy strip for lead frame is obtained.
[0032] The prepared copper alloy strip was subjected to performance tests, wherein the mass percentages of each element in the copper alloy strip are as follows:
[0033] Ni: 1.397%; Si: 0.6491%; Mg: 0.934%; Co: 1.579%; Ti: 0.038%; Y: 0.142%, the remainder being copper and inevitable impurities.
[0034] The hardness of the copper alloy strip prepared in Example 2 is HV=261.5, and the tensile strength is σ b =853.2Mpa, electrical conductivity = 55.4%IACS, yield strength σ 0.2 =752.7MPa.
[0035] Example 3
[0036] 0.6g titanium powder, 1.2g magnesium powder, 5g Cu-Y alloy (wherein the Y content is 20wt.%) are sealed in a pure copper tube and fixed on the mechanical arm of a vacuum induction furnace, and 943.2g copper powder, 19g nickel powder, 6g silicon powder, and 5g cobalt powder are added to the crucible of the vacuum induction furnace. The vacuum induction furnace is evacuated to below 15Pa, and the protective atmosphere argon gas is introduced to 0.05MPa, and then the induction power supply is introduced to start heating. When all the solids in the crucible are melted and heated to about 1500℃, the induction current is turned off, and the mechanical arm is quickly operated to immerse the pure copper tube containing titanium powder, magnesium powder, and Cu-Y alloy under the melt liquid surface, and the mechanical arm is lifted, and the induction current is turned on to continue to keep warm for 3min, and casting is performed after keeping warm. After casting is completed, it is cooled for about 30min and taken out, and the ingot is milled, and then placed in a muffle furnace and heated to 900℃ at a heating rate of 5℃ / min and kept warm for 3h. After the insulation is completed, the ingot is taken out and water-cooled. The ingot after solutionization is placed in a muffle furnace at 750℃ for 40 minutes, taken out and sent to a hot rolling mill for a rolling process with a pressing amount of 20% per pass, and the final rolling amount is 50%. Then it is sent to a cold rolling mill and rolled at a speed of 10% per pass to a plate thickness of about 2mm, and then the plate is annealed at 400℃ for 5h, and then the plate is rolled at a speed of 10% per pass to a plate thickness of 0.45mm. Then the plate is annealed at 300℃ for 5h, and finally the plate is rolled at a speed of 10% per pass to a plate thickness of 0.2mm (the possible edge cracks are removed in time during the cold rolling process), and a multi-component synergistically strengthened copper alloy strip for lead frame is obtained.
[0037] The prepared copper alloy strip was subjected to performance tests, wherein the mass percentages of each element in the copper alloy strip are as follows:
[0038] Ni: 1.901%; Si: 0.601%; Mg: 0.118%; Co: 0.497%; Ti: 0.059%; Y: 0.008%, and the remainder is copper and inevitable impurities.
[0039] The hardness of the copper alloy strip prepared in Example 3 is HV=266.7, and the tensile strength is σ b =855.4Mpa, electrical conductivity =55.8%IACS, yield strength σ 0.2 =758.9MPa.
[0040] Comparative Example 1
[0041] 964g copper powder, 19g nickel powder, 6g silicon powder and 11g cobalt powder are added to the crucible of the vacuum induction furnace. The vacuum induction furnace is evacuated to below 15Pa, and the protective atmosphere argon gas is introduced to 0.05MPa, and then the induction power supply is introduced to start heating. When all the solids in the crucible are melted and the temperature rises to about 1500℃, the induction current is turned off and the casting is carried out quickly. After the casting is completed, it is cooled for about 30 minutes and taken out. The ingot is milled and then placed in a muffle furnace and heated to 900℃ at a heating rate of 5℃ / min and kept warm for 4h. After the insulation is completed, the ingot is taken out and water-cooled. The ingot after solid solution is sent to the cold rolling mill and rolled at a speed of about 20% per pass until the plate thickness is about 0.2mm, and a copper alloy strip is obtained.
[0042] The prepared copper alloy strip was subjected to performance tests, wherein the mass percentages of each element in the copper alloy strip are as follows:
[0043] Ni: 1.901%; Si: 0.583%; Co: 1.082%; the remainder is copper and inevitable impurities.
[0044] The hardness of the copper alloy strip prepared in Comparative Example 1 is HV=209.2, and the tensile strength is σ b =650.5Mpa, electrical conductivity = 38.4%IACS, yield strength σ 0.2 =553.8MPa.
[0045] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A multi-component synergistically reinforced copper alloy strip for lead frame, characterized in that: The following ingredients are included in mass percentage: Ni: 0.9% ~ 3.0%; Si: 0.3% ~ 1.3%; Mg: 0.06% ~ 0.18%; Co: 0.5% ~ 1.5%; Ti: 0.02% ~ 0.1%; Y: 0.05% ~ 0.15%, the remainder is copper and unavoidable impurities.
2. The method for preparing the multi-component synergistically reinforced copper alloy strip for lead frame according to claim 1, characterized in that: The following steps are involved: (1) Ingredients: Weigh titanium powder, magnesium powder, Cu-Y alloy, silicon powder, cobalt powder, nickel powder and copper powder; (2) Melting: Weighed titanium powder, magnesium powder, and Cu-Y alloy are sealed in a pure copper tube and fixed on the robot arm of a vacuum induction furnace, and copper powder, nickel powder, silicon powder, and cobalt powder are added to the crucible of the vacuum induction furnace; after the vacuum induction furnace is evacuated, a protective atmosphere is introduced to 0.05 MPa, and then the crucible is heated until all the solids in the crucible are melted and the temperature is raised to 1500° C., the induction current is turned off, and the robot arm is quickly operated to immerse the pure copper tube containing the titanium powder, magnesium powder, and Cu-Y alloy under the melt surface, the robot arm is lifted and the induction current is turned on to continue to keep the temperature for 2 min-5 min, and casting is performed after the temperature is kept, and cooling is performed after the casting is completed to obtain an ingot; (3) Solid solution: The ingot obtained in step (2) is subjected to surface milling treatment, and then placed in a muffle furnace and heated to 800° C. to 900° C. and kept at this temperature for 3 h to 5 h. After the heat preservation is completed, the ingot is taken out and water-cooled; (4) Hot rolling: the solution-solution ingot is kept at 700°C to 800°C for 15 to 40 minutes, taken out and sent to a hot rolling mill for rolling with a reduction of 15% to 35% per pass, and the final rolling amount is 50%; (5) Cold rolling: the sample after rolling in step (4) is sent to a cold rolling mill and rolled at a speed of 8% to 12% per pass to a plate thickness of 1.5 mm to 2.5 mm. The plate is then annealed at 400° C. to 450° C. for 3 h to 5 h. The plate is then rolled at a speed of 8% to 12% per pass to a plate thickness of 0.3 mm to 0.5 mm. The plate is then annealed at 300° C. to 350° C. for 3 h to 5 h. Finally, the plate is rolled at a speed of 8% to 12% per pass to a plate thickness of 0.15 mm to 0.25 mm.
3. The preparation method according to claim 2, characterized in that: The Y content in the Cu-Y alloy is 15wt.% to 25wt.%.
4. The preparation method according to claim 2, characterized in that: The protective atmosphere in step (2) is argon or nitrogen.
5. The preparation method according to claim 2, characterized in that: The heating rate in step (3) is 3°C to 6°C / min.
Citation Information
Patent Citations
Cu-Ti-Ge-Ni-X Cu alloy material and preparation method thereof
CN110885937A
Preparation method of Cu-Cr-Si-Ti copper alloy plate strip
CN112322917A
Preparation process of copper alloy material for short-process lead frame
CN113699397A
Lead frame copper alloy strip with excellent comprehensive performance for packaging of extremely-large-scale integrated circuit chip and preparation method of lead frame copper alloy strip
CN117305651A
Method for simultaneously improving mechanical property and conductivity of Cu-Ni-Si-Co copper alloy
CN117305740A
Cited By
Preparation method of ultrahigh-strength conductive copper alloy strip
CN121874562A